Industrial Revolution 4.0 In Mechanical Engineering: A Literature Review On The Application Of Iot And Automation In Production Systems - Prananta, Arie Wahyu; Dwiyanto, Dwiyanto (Journal of Renewable Engineering, 2025)
The Industrial Revolution 4.0 has revolutionized the mechanical engineering production paradigm through the integration of digital technologies such as the Internet of Things (IoT), cyber-physical systems (CPS), and intelligent automation. This study aims to evaluate the strategic role of IoT and automation in realizing an adaptive, efficient, and sustainable mechanical engineering production system. Using a qualitative approach with a literature review method, this study analyzes the latest findings from relevant scientific sources over the past five years. The results of the review indicate that the implementation of IoT contributes to increased efficiency through predictive maintenance, reduced downtime, and real-time data-driven decision-making. On the other hand, the evolution of automation includes precision robotics, cloud-based CNC, and intelligent PLCs that enhance production flexibility and quality. However, several challenges have been identified, such as limited digital human resources, inadequate infrastructure, and system interoperability issues. Therefore, adaptive strategies such as continuous technical training, cross-sector collaboration, and strengthening industrial digitalization policies are needed. This study concludes that the integration of IoT and automation is a key foundation for the transformation of mechanical engineering towards inclusive and sustainable smart manufacturing, and emphasizes the importance of synergy between technology, people, and policies in supporting a systemic and contextual industrial revolution.